Halitosis: Basic Principles About its Origin and Treatment Narrative Review - Barba DDS, Lucía (2018)
Halitosis is the presence of an unpleasant smell that emanates from the oral cavity. The etiology of halitosis is multifactorial, existing non oral, oral and extraoral causes. The volatile sulphur compounds (VSC): hydrogen sulfide and methyl mercaptan are the prominent elements of malodour. Intraorally there is a significant correlation between VSC concentrations and periodontopathogenic bacteria. In patients with no gum disease the halitosis is originated mainly in the dorsal surface of the tongue, so cleaning or brushing it is an effective method to prevent or decrease halitosis. There are multiple chemical options for the treatment of the malodour that will depend on the origin and severity of it. This article reviews the origin and mechanical and chemical treatments that are available.